The Effectiveness of Diagnostic Assessments and GeoGebra-Assisted Learning on Learning Outcomes Reviewed from Learning Styles - Salsinha, Cecilia Novianti; Fitriani, Fitriani; Bete, Hendrika; Hall, Eric Steven (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2025)
This study aims to analyze the effectiveness of providing cognitive and non-cognitive diagnostic (learning style) assessments and recognizing students' learning styles before the learning process occurs. The results of this study show that, typically, the diagnostic assessment process is not implemented before learning activities begin, and that the learning process proceeds without first taking into account the learning style of the students. This study also analyzes the effectiveness of the use of GeoGebra in learning as a solution to facilitating various student learning styles. The research was carried out in 2 schools, namely SMA Negeri 2 Kefamenanu and SMA Katolik Warta Bakti Kefamenanu, utilizing a Pre-Experimental design, with a total of 53 students chosen by a purposive sampling technique. Data were collected using questionnaires and test questions, then analyzed using the Kruskal-Wallis and Wilcoxon Signed Test methods to compare the student groups from each school. The results indicate that the average mathematical diagnostic assessment score was 16.4553. After utilizing GeoGebra during learning and focusing on student learning styles, the students' average mathematical ability score increased to 62. This result is supported by the Kruskal-Wallis Test and Wilcoxon Signed Test, indicating that the average of the mathematical ability score from the diagnostic assessment reaches near-equilibrium after the students are exposed to GeoGebra. The increase in students' ability by 55% on the N-Gain Test shows that learning by utilizing GeoGebra is quite effective in improving students' mathematical skills. These results lead to the conclusion that learning by using GeoGebra during learning after cognitive diagnostic assessments and paying attention to students' learning styles is the best way to improve student learning outcomes.